Wheat stem rust in Brazil and other countries of the southern cone of South America - Coelho, E. T. (Pesquisa Agropecuaria Brasileira, 2014)
From 1979 to 1981, in the Brazilian wheat regions, 1.611 samples of wheat stem rust (Puccinia graminis Pers. f.sp. tritici Eriks & Henn) were collected and studied. The new system has been described to designate the different virulence formula determined in Brazil. The races G1 (11), G3 (17), G4 (17/61), G7 (17/63), G9(15/65), G11 (11/74), G12(11/78), G13 (15/78), G14(17/80), G15 (11/81), G16 (17/81), G17 (/81), G18, G19 and G20 were identified. Race G14 was detected for the first time on samples collected in 1979; races G15, G16 and G17 in 1980, and G18, G19 and G20, in 1981. In 1979 the most prevalent race was G11 (50%); in 1980 the complex G11 + G15 (62%); in 1981 G17 (42%) and G15 (25%). The genes Sr 22, Sr 24, Sr 25, Sr 26,Sr 27,Sr 31, Sr 32 and Sr 33, separately, confer resistance to all identified races. The race G12 was identified on the four samples studied from Bolivia; the races G11, G13, G15, G17 and G20 on 28 samples from Paraguay, and the races G9, G13, G15, G17, G18, G19 and G20 on 28 samples from Uruguay.